Assessing Bone Mineral Density Among Female Medical Students Of Pakistan: Unveiling The Impact Of Lifestyle Factors On Skeletal Health- An Analytical Cross-Sectional Study - Kulsoom, Afifa; Noor, Mehreen; Naeem, Eeman; Noreen, Khola; Mansoor, Muhammad Umar; Mahmood, Tahir (Journal of Rawalpindi Medical College, 2025)
Objective: To assess the frequency of low bone mineral density (BMD) and its association with lifestyle factors among female medical students in Pakistan. Methods: A cross-sectional study was conducted at ---- between January and June 2025. A total of 184 undergraduate female medical students were included using non-probability consecutive sampling. BMD was assessed using Quantitative Ultrasound (QUS) of the calcaneus, with T-scores recorded for each participant. Data on demographic details and lifestyle factors, including physical activity, dietary intake, BMI, and screentime, were collected through a structured questionnaire. Statistical analysis was performed using SPSS 26.0. Pearson correlation and chi-square tests were applied, with p-values less than 0.05 considered statistically significant. Results: Among 184 female participants, the mean age was 22.00 ± 1.056 years. QUS revealed that only 36 students (19.6%) had normal bone mineral status, 134 (72.8%) had osteopenia, and 14 (7.6%) had osteoporosis. A significant positive correlation was observed between BMI and T-score (r = 0.347, p value of 0.000). Bone status was significantly associated with year of study (p = 0.002), physical activity (p 0.000), carbonated drink intake (p = 0.009), overeating (p = 0.005), and coffee consumption (p = 0.038). Conclusion: Most young female medical students had low BMD, with modifiable lifestyle factors contributing significantly, highlighting the need for early screening and preventive strategies targeting bone health in this vulnerable population. Keywords: Bone Density, Osteoporosis, Lifestyle, Students, Medical